Remote onboarding and beyond: Fostering organizational citizenship behavior through psychological channels - Somu, Subbulakshmi; Ali, Noor Azman (University of Economics in Katowice, 2025)
Aim/purpose – The purpose of this paper is to investigate the influence of remote onboarding practices on organizational citizenship behavior. This study addresses the gap in understanding how remote onboarding influences employees’ behavior through psychological processes. Design/methodology/approach – The study utilizes a quantitative research approach, analyzing data collected from 608 respondents through structured surveys. It employs a serial mediation process to explore the roles of psychological contracts and psychological ownership in the relationship between remote onboarding and organizational citizenship behavior. Findings – The study reveals that remote onboarding programs have a significant impact on organizational citizenship behavior by fostering a psychological contract and psychological ownership. These factors act as mediators, linking effective onboarding practices to enhanced employee organizational citizenship behavior. Research implications/limitations – The findings provide valuable insights into management practices, highlighting the importance of prioritizing comprehensive digital onboarding strategies for organizations. However, the study’s reliance on self-reported data may introduce biases, and future research should consider conducting longitudinal studies to validate the results. Originality/value/contribution – This research contributes to the existing literature on social exchange theory and social identity theory by elucidating the psychological mechanisms that connect remote onboarding to organizational citizenship behavior. It offers practical recommendations for enhancing digital onboarding processes to promote employee engagement and improve organizational outcomes.